Urban and rural differences in out-of-hospital cardiac arrest in Ireland. (June 2015) - Masterson, S.; Wright, P.; O'Donnell, C.; Vellinga, A.; Murphy, A.W.; Hennelly, D.; Sinnott, B.; Egan, J.; O'Reilly, M.; Keaney, J.; Bury, G.; Deasy, C.
Abstract: Background: More than a third of Ireland's population lives in a rural area, defined as the population residing in all areas outside clusters of 1500 or more inhabitants. This presents a challenge for the provision of effective pre-hospital resuscitation services. In 2012, Ireland became one of three European countries with nationwide Out-of-Hospital Cardiac Arrest (OHCA) register coverage. An OHCA register provides an ability to monitor quality and equity of access to life-saving services in Irish communities. Aim: To use the first year of national OHCAR data to assess differences in the occurrence, incidence and outcomes of OHCA where resuscitation is attempted and the incident is attended by statutory Emergency Medical Services between rural and urban settings. Methods: The geographical coordinates of incident locations were identified and co-ordinates were then classified as 'urban' or 'rural' according to the Irish Central Statistics Office (CSO) definition. Results: 1798 OHCA incidents were recorded which were attended by statutory Emergency Medical Services (EMS) and where resuscitation was attempted. There was a higher percentage of male patients in rural settings (71% vs. 65%; p = 0.009) but the incidence of male patients did not differ significantly between urban and rural settings (26 vs. 25 males/100, 000 population/year p = 0.353). A higher proportion of rural patients received bystander cardiopulmonary resuscitation (B-CPR) 70% vs. 55% ( p ≤ 0.001), and had defibrillation attempted before statutory EMS arrival (7% vs. 4% ( p = 0.019), respectively). Urban patients were more likely to receive a statutory EMS response in 8 min or less (33% vs. 9%; p ≤ 0.001). Urban patients were also more likely to be discharged alive from hospital (6% vs. 3%; p = 0.006) (incidence 2.5 vs. 1.1/100, 000 population/year; p ≤ 0.001). Multivariable analysis of survival showed that the main variable of interest i.e. urban vs. rural setting was also independently associated with discharge from hospital alive (OR 3.23 (95% CI 1.43–7.31)). Conclusion: There are significant disparities in the incidence of resuscitation attempts in urban and rural areas. There are challenges in the provision of services and subsequent outcomes from OHCA that occur outside of urban areas requiring novel and innovative solutions. An integrated community response system is necessary to improve metrics around OHCA response and outcomes in rural areas.